2013
DOI: 10.1007/s00520-013-1786-7
|View full text |Cite
|
Sign up to set email alerts
|

Reducing disparity in outcomes for immigrants with cancer: a qualitative assessment of the feasibility and acceptability of a culturally targeted telephone-based supportive care intervention

Abstract: Purpose: Australia has one of the most culturally diverse populations in the world.Immigrant cancer patients' poorer outcomes compared to English-speaking patients confirm the need for culturally sensitive supportive care interventions. The aim of this study was to (1) identify cultural sensitivities important to the acceptability of a telephone-based supportive care intervention (2) identify cultural barriers and facilitators to intervention participation. Methods:Patients and carers attending Chinese or Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…Of the six included articles, three were conducted in Australia involving samples of Arab, Greek, and Chinese migrants,[91041] two studies were conducted in Jordan with samples comprised of caregivers[3142] whereas the final study from the USA compared the needs of American and Egyptian cancer patients. [43] Four of the studies employed quantitative methodology, with two of the Australian studies using the supportive care needs survey (SCNS), translated into Arabic whereas the Jordanian studies used Arabic translations of the caregiver's need scale,[31] and the family inventory of needs - pediatric - II.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the six included articles, three were conducted in Australia involving samples of Arab, Greek, and Chinese migrants,[91041] two studies were conducted in Jordan with samples comprised of caregivers[3142] whereas the final study from the USA compared the needs of American and Egyptian cancer patients. [43] Four of the studies employed quantitative methodology, with two of the Australian studies using the supportive care needs survey (SCNS), translated into Arabic whereas the Jordanian studies used Arabic translations of the caregiver's need scale,[31] and the family inventory of needs - pediatric - II.…”
Section: Resultsmentioning
confidence: 99%
“…In a quantitative study conducted by Butow et al .,[9] the unmet needs of Arabic ( n = 57), Greek ( n = 79), Chinese ( n = 114), and Anglo-Australian patients ( n = 319) were compared. A greater proportion of the immigrant sample ( n = 277) reported unmet needs compared to Anglo-Australians.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient navigation programs have received increasing attention for their effectiveness in improving access to quality cancer care and system efficiency [25]. A recent study of the feasibility of a culturally targeted patient navigation program has shown that such a service is welcomed by potential consumers, who viewed it as a useful means to cater to their needs and preferences [26].…”
Section: Discussionmentioning
confidence: 99%